The role of protonation processes in the gradual formation of the light-adapted charge-separated state of photosystem II - Magyar, Melinda; Sipka, Gábor; Domonkos, Ildikó; Chen, Xiaojun; Wang, Xu; Han, Guangye; Shen, Jian-Ren; Lambrev, Petar H.; Garab, Győző (Frontiers in Photobiology, 2025)
Earlier, we discovered that to reach the maximum chlorophyll-a (Chl-a) fluorescence level of photosystem II (PSII) in diuron-treated samples, and thus PSIIL, the light-adapted charge-separated state, multiple excitations with sufficiently long Δτ waiting times between excitations are required. Experiments of Chl-a fluorescence, elicited by single-turnover saturating flashes (STSFs), revealed that the Δτ1/2 half-waiting times between flashes depended on the lipid content of the reaction centre (RC) and on the temperature. We hypothesized that the gradual formation of PSIIL depends on protonatable residues (and bound water molecules) at the donor side of the RC. Here, we tested this hypothesis: we used diuron-treated isolated PSII core complexes of Thermostichus vulcanus and determined the pH dependence of Δτ1/2 and other Chl-a fluorescence parameters at different temperatures. Data recorded at 5°C revealed moderate and steep increases of Δτ1/2 between pH 5.0 and 6.5, and 6.5 and 8.0, respectively. Much weaker pH dependences were seen at cryogenic temperatures (−20 and −60°C), indicating the role of structural plasticity in the protonation-dependent reorganizations. Similar to the strong pH dependence of Δτ1/2 at 5°C, the magnitude of the F1 fluorescence level, induced by the first STSF, displayed moderate and steep increases between pH 5.0 and 6.5, and 6.5 and 8.0, respectively, at all temperatures. Corroborating data were received from fast Chl-a fluorescence transient measurements. Hence, our data provide experimental support to the hypothesized role of protonation processes in the formation of PSIIL. The protonophores, CCCP and FCCP significantly increased the Δτ1/2 at pH 6.0 and essentially eliminated the pH dependence of the F1 fluorescence level. These data provide experimental support to our hypotheses on the role of protonatable residues in determining the structural dynamics of PSII RCs.